2023
DOI: 10.3389/fmed.2022.1106312
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for prolonged length of hospital stay in patients with osteoporotic femoral neck fracture: A 5-year retrospective study

Abstract: Prolonged length of stay (LOS) in osteoporotic femoral neck fracture patients increased the hospital care cost and demonstrated in-hospital complications. This study aimed to develop an ease-of use predictive model of prolonged LOS in osteoporotic femoral neck fracture patients. In this 5-year retrospective study, the medical charts of 255 patients admitted to hospital with an osteoporotic femoral neck fracture resulting from a simple fall from January 2014 to December 2018 were reviewed. Multivariable fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(52 reference statements)
0
3
1
Order By: Relevance
“…On the other hand, this study result is lower than the study conducted in Nigeria (63%) [17] and Thailand (54.9%) [52]. In the case of Nigeria, this discrepancy may be due to the study period and the lower cutoff points used, which were at least 7 days, which is less than the cutoff point used in this study.…”
Section: Discussioncontrasting
confidence: 79%
“…On the other hand, this study result is lower than the study conducted in Nigeria (63%) [17] and Thailand (54.9%) [52]. In the case of Nigeria, this discrepancy may be due to the study period and the lower cutoff points used, which were at least 7 days, which is less than the cutoff point used in this study.…”
Section: Discussioncontrasting
confidence: 79%
“…In those studies, the American Society of Anesthesiologists physical status classification system was used to classify the physical status while our study used the MFAC score to categorize functional ambulation ability. Recently, a similar study [25] predicted LOS in pre-operative femoral neck fracture patients using machine learning techniques and they concluded that the age, ASA score, BMI, and time from injury to surgery were strong predictors of prolonged LOS. Their results were mostly compatible with our findings -we also discovered that age and physical status, reflected by MFAC, were strong predictors of prolonged LOS across various high-performing models.…”
Section: Discussionmentioning
confidence: 99%
“…Unique to our study, we have data attributes that are not commonly found in other geriatric fragility fracture databases. Most of the studies done on geriatric fragility fracture only have basic data features, such as gender and age [22][23][24][25], and some easily attainable data [24,25], such as height, weight, and the International Classification of Disease (10th Revision) code, etc. Our study had more data features to more accurately reflect the situation of each holistically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation